Mule deer juniper use is an unreliable indicator of habitat quality: Comments on Coe et al. (2018). Issue 4 (8th May 2019) - Maestas, Jeremy D.; Hagen, Christian A.; Smith, Joseph T.; Tack, Jason D.; Allred, Brady W.; Griffiths, Tim; Bishop, Chad J.; Stewart, Kelley M.; Naugle, David E.
Abstract : A recent paper by Coe et al. (2018) calls into question juniper removal for sagebrush obligate species based on results from a correlative study of mule deer habitat use. Our rebuttal clarifies limitations of inference in their study regarding mule deer habitat quality, highlights the importance of winter forage on demography with omitted literature, and discusses the diverse nature of the author's study area and the spatial overlap between mule deer winter range and known juniper treatments for sage‐grouse.